Supercritical extraction of value-added compounds from empty fruit bunch: An optimization study by response surface methodology - Yim, S.C. (Elsevier, 2019)
The extraction of value-added compounds from oil palm empty fruit bunches (EFB) using supercritical CO2 (SCCD) and water as a co-solvent (modifier) was investigated. The optimization study of extraction was performed using response surface methodology with central composite rotatable design. Extraction parameters including temperature, pressure, and particle size were optimized and determined. The regression model developed gave accurate predictions and fitted well with the experimental results, yielding a coefficient of determination (R2) of 0.93. Based on the model, the optimum extraction conditions were predicted to be at 75Â°C, 34 MPa and particle size of 0.65-0.75 mm, with a prediction yield of 5.47. This condition was validated by experimental runs which produced an average yield of 5.46 wt. The supercritical extract of EFB was then characterized by GC-MS and compared with an extract obtained by Soxhlet extraction using hexane. The quantity and quality of the extract obtained by SCCD was superior to that of Soxhlet extraction. Â© 2019 Elsevier Inc. All rights reserved.